Harvard Business Review on Finding & Keeping the Best People - Harvard Business School (Boston, Massachusetts Harvard Business Press, 2011)
This collection of HBR articles will help you: look for good people in all the right places; interview more effectively; make, and keep compelling promises to candidates and employees; mitigate the risks of hiring stars from other companies; coach and mentor to shore up commitment; stretch promsing employees' responsibilities; rotate high performers into a variety of teams; and, reverse the female brain drain.
Include Index
Keywords: Employee retention -- Employees--Recruiting -- Personnel management